Abcc9 is required for the transition to oxidative metabolism in the newborn heart. Issue 7 (19th March 2014) - Fahrenbach, John P.; Stoller, Douglas; Kim, Gene; Aggarwal, Nitin; Yerokun, Babatunde; Earley, Judy U.; Hadhazy, Michele; Shi, Nian‐Qing; Makielski, Jonathan C.; McNally, Elizabeth M.
ABSTRACT: The newborn heart adapts to postnatal life by shifting from a fetal glycolytic metabolism to a mitochondrial oxidative metabolism. Abcc9, an ATP‐binding cassette family member, increases expression concomitant with this metabolic shift. Abcc9 encodes a membrane‐associated receptor that partners with a potassium channel to become the major potassium‐sensitive ATP channel in the heart. Abcc9 also encodes a smaller protein enriched in the mitochondria. We now deleted exon 5 of Abcc9 to ablate expression of both plasma membrane and mitochondria‐associated Abcc9 ‐encoded proteins, and found that the myocardium failed to acquire normal mature metabolism, resulting in neonatal cardiomyopathy. Unlike wild‐type neonatal cardiomyocytes, mitochondria from Ex5 cardiomyocytes were unresponsive to the KATP agonist diazoxide, consistent with loss of KATP activity. When exposed to hydrogen peroxide to induce cell stress, Ex5 neonatal cardiomyocytes displayed a rapid collapse of mitochondria membrane potential, distinct from wild‐type cardiomyocytes. Ex5 cardiomyocytes had reduced fatty acid oxidation, reduced oxygen consumption and reserve. Morphologically, Ex5 cardiac mitochondria exhibited an immature pattern with reduced cross‐sectional area and intermitochondrial contacts. In the absence of Abcc9, the newborn heart fails to transition normally from fetal to mature myocardial metabolism.—Fahrenbach, J. P., Stoller, D., Kim, G., Aggarwal, N., Yerokun, B., Earley, J. U., Hadhazy, M., Shi, N.‐Q., Makielski, J. C., McNally, E. M. Abcc9 is required for the transition to oxidative metabolism in the newborn heart. FASEB J . 28, 2804–2815 (2014). www.fasebj.org